Toxic Epithelial Corneal Edema Due to Insulating Material Exposure - Erdag, Murat; Canleblebici, Mehmet; Dal, Ali; Yıldırım, Hakan; Balbaba, Mehmet; Aydemir, Orhan (My University, 2024)
In this case series, 19, 21, and 33 years old male patients who complain of blurred vision presented with corneal edema after using insulation material in the workplace. Isocyanate is a raw material used in the production of all polyurethane materials and is used as a basic material in construction and industrial products. We aimed to emphasize that corneal toxicity may be developed due to exposure to diphenylmethane diisocyanate and polymethylene polyphenyl isocyanate, which are used as insulation materials, and that both employees and ophthalmologists should take caution about this rare situation.
Keywords: Isocyanates; Corneal Edema; Chemical Corneal Injury